2019
DOI: 10.3390/ma12091437
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bi3+ Doping on the Optical and Electric-Induced Light Scattering Performance of PLZT (8.0/69/31) Transparent Ceramics

Abstract: Lanthanum modified lead zirconate titanate (abbreviated as PLZT) Electro-Optical ceramics with various Bi concentration were prepared by a hot-press process. The PLZT ceramic samples all present a single perovskite structure with no second phase detected. Bi3+ ion was considered to mainly enter the A-site of perovskite ABO3 structure of PLZT ceramics by the X-Ray Diffractionanalysis. The maximum permittivity (εm) of the PLZT samples decreased obviously as Bi concentration increased, while their remnant polariz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…The above macroscopic analysis of explaining the high EO effect is reasonable but still not comprehensive and profound. Among the references we have found so far, there is some literature [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]28,29] that studies ferroelectric domains of the PMN-PT ceramics, but lacks very clear domain morphology characterization. We obtained the domain morphology and studied the domain reversal (polarization behavior) from microscopic perspective to further demonstrate instability of the intermediate ferroelectric state.…”
Section: Domain Structure and Polarization Reversalmentioning
confidence: 99%
See 4 more Smart Citations
“…The above macroscopic analysis of explaining the high EO effect is reasonable but still not comprehensive and profound. Among the references we have found so far, there is some literature [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]28,29] that studies ferroelectric domains of the PMN-PT ceramics, but lacks very clear domain morphology characterization. We obtained the domain morphology and studied the domain reversal (polarization behavior) from microscopic perspective to further demonstrate instability of the intermediate ferroelectric state.…”
Section: Domain Structure and Polarization Reversalmentioning
confidence: 99%
“…Utilizing the high EO effect of PMN-PT to design optical devices with tuning capability such as TOF is very valuable; however, application studies of the PMN-PT ceramics are rarely reported [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. To realize the application of the PMN-PT transparent ceramics in EO tunable filters, we first tested TFPF based on 2/75/25 ceramic sheet.…”
Section: Application In Tunable Filtermentioning
confidence: 99%
See 3 more Smart Citations